การเก็บกลับคืนทองคำและทองแดงจากสินแร่ซัลไฟด์ของแหล่งแร่ภูทับฟ้า - พีท หอมชื่น (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The purpose of this research is to recovery of gold and copper from sulphide ores of Phu Thap Fah deposits, Thug khum Limited in Loei province, Thailand. The mineralogical study of the ores using microscope, Electron Probe Micro- Analyzer (EPMA) and X-Ray Diffractometer (XRD) indicates that the sulphide ores contain high iron mineral as pyrrhotite and copper mineral as chalcopyrite which is formed from the exsolution of pyrite (FeS2) at high temperature. The mapping of gold, copper and iron reveal that gold associated with iron as (pyrrhotite) rather than copper (chalcopyrite). In recovery of gold and copper by froth flotation technique, copper concentrate has found to be the mixture of Cu-Fe-S as chalcopyrite and Fe-S as pyrrhothite. The flotation test show that gold and copper can be recovered as copper concentrate. The 2 ppm of Au in the feed can be upgraded to be 35 ppm Au in the copper concentrate with 65 % recovery. The 0.7 % Cu in the feed can also be upgraded to 15 % Cu in the copper concentrate at 90 % recovery.